FAKTOR SOSIAL EKONOMI YANG MEMPENGARUHI PENGAMBILAN KEPUTUSAN PETANI DALAM SISTEM PENJUALAN SAYURAN WORTEL (Suatu Kasus Petani Sayuran Desa Nyalindung di Kecamatan Cugenang Kab. Cianjur) - Marina, Ida; Sulandjari, Kuswarini (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2013)
The purpose of this study was to determine the influence of socioeconomic factors on farmer's decision to sell the carrot farming and income, as well as the influence the farmer's decision to sell the results of carrot farming to the production cost. The method used in this study is a survey method. Mechanical determination of respondent do with the determination of the samples was determined by the census were traced to the farmer who has completed the sale obtained by 31 farmers who sell directly to the market and 14 farmers who sell blow. The results showed that the carrot farm income is influenced by socio-economic factors; land area, age of farmers, farming experience, education of farmers, dependents, pricing, and cost aspects. Decision grower selling single stroke and sales are directly influenced by the cost of production, while farmers who sell directly to the market charged harvesting, washing and transporting and prices received relatively unchanged in accordance with the laws of the market. Farmer's decision to sell the results of farming carrot effect on revenue.